Coastal Sami revitalization and rights claims in Finnmark (North Norway) - two aspects of one issue? Preliminary observations from the field - Lätsch, Angelika (Samisk senters skriftserie, 2012)
The focus of this paper is on the rights claim processes and the revitalization process of the indigenous coastal Sami population in northern Norway. By examining the available research literature and reflecting upon preliminary observations gathered in anthropological fieldwork, I examine how the fight for resource protection and special resource rights are interlinked with Sami identity management. To do so, I analyze the different levels of the claiming of rights in their specific setting throughout time, with a special focus on the period from 1990 onwards. I will show how the actors, the argumentations, and strategies have changed over the course of time leading to the current ‘indigenization’ of the rights claim process.